Subcutaneous Histiocytoid Sweet Syndrome Associated with Crohn Disease in an Adolescent - Rosa María Fernández-Torres; Susana Castro; Ana Moreno; Roberto Álvarez; Eduardo Fonseca (Hindawi Limited, 2014)
We report a case of subcutaneous histiocytoid Sweet syndrome in an adolescent with Crohn disease. A 14-year-old boy with a 1-year history of ileocolonic and perianal Crohn disease, treated with infliximab and azathioprine, was admitted to the Pediatrics Department with malaise, abdominal pain, bloody diarrhea, and fever (39°C) from 15 days ago. Two days later, he developed cutaneous lesions consisting of tender, erythematous, and violaceous papules and nodules scattered over his legs, soles, and upper extremities. Laboratory studies revealed neutrophilia, microcytic anemia, and elevation of both erythrocyte sedimentation rate and C-reactive protein rate. A skin biopsy specimen showed deep dermal and predominantly septal inflammatory infiltrate in the subcutaneous tissue composed of polymorphonuclears, eosinophils, and mononuclear cells of histiocytic appearance. These histiocytoid cells stained positive for myeloperoxidase. Subcutaneous Sweet syndrome is a rare subtype of acute neutrophilic dermatosis, in which the infiltrate is exclusively or predominantly located in the subcutaneous tissue, causing lobular or septal panniculitis. It is often described in patients with an underlying haematological disorder or caused by drugs, but very rare in patients with inflammatory bowel disease, especially in childhood or adolescence. To our knowledge, this is the first case of subcutaneous histiocytoid type in a paediatric patient.